Membrane PD-L1 expression and soluble PD-L1 plasma levels in idiopathic pulmonary fibrosis—a pilot study - Jovanovic, Dragana; Milenkovic, Marina Roksandic; Stevuljevic, Jelena Kotur; Markovic, Jelena; Ceriman, Vesna; Kontic, Milica; Trifunovic, Vesna Skodric (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Background: Idiopathic pulmonary fibrosis (IPF) has common risk factors with cancer and significant similarities in the pathobiology process, both diseases having poor outcomes. Immune checkpoint PD-L1 has become the target of checkpoint inhibitory therapy that unleashes antitumor T cells and has revolutionized cancer treatment. This is a pilot study exploring membrane immune checkpoint PD-L1 expression in human IPF lung tissue samples and its soluble form, soluble PD-L1 (sPD-L1) plasma concentrations in IPF patients, in order to investigate potential role of PD-L1 as an IPF biomarker. Methods: Twelve human IPF lung tissue samples (formalin-fixed, paraffin-embedded) obtained by surgical biopsy, have been tested for PD-L1 expression by PD-L1 IHC 22C3 pharmDx assay, while plasma samples for examination of sPD-L1 forms, PD-L1 (B7-H1/CD274) blood concentration, originated from 23 patients with IPF who did not undergo surgical biopsy. Results: Membrane PD-L1 expression in IPF lung tissue samples was positive to overexpression of PD-L1 in 9 samples out of 12. Only very few cells in the interstitium have shown a discrete PD-L1 expression, but not of a membrane type. As for sPD-L1 forms, we have found elevated concentrations of sPD-L1 in the serum of IPF patients 314.3 ng/L (117.7–483.1 ng/L), significantly higher compared with healthy control group 91.0 ng/L (52.4–119.7 ng/L), P